Vibration based piezoelectric energy harvesting utilizing bridgeless rectifier circuit - Mahidur R. Sarker; Azah Mohamed; Ramizi Mohamed (Penerbit Universiti Kebangsaan Malaysia, 2016)
The energy harvesting technique has the capability to build autonomous, self-powered electronic systems that does not depend on the battery power for driving the low power electronics devices. In this paper, a voltage doubler and bridgeless boost rectifier power electronic converter is proposed to increase the energy harvesting output voltage from piezoelectric vibration based transducer. The conventional full-wave diode bridge rectifier and boost converter for energy harvesting system increases significant voltage drop and power losses in the circuit. However, the proposed voltage doubler and bridgeless boost rectifier circuit reduce the voltage drop and power loses in the circuit and thus increases the efficiency of the circuit. The proposed voltage doubler and bridgeless boost rectifier circuit step-up the output voltage up to 3 V DC from an input voltage of 1.9 V AC.